1969
DOI: 10.1037/h0027968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the observer condition, instructional set, reward schedule, and sex of subject upon performer and observer.

Abstract: Frustration theory has been employed to interpret the findings of several investigations which have indicated that performance of an instrumental response is better under conditions of noncontinuous as compared with continuous reward. Studies have shown this effect when the subject performed individually or in the presence of a passively observing peer, but not when the peer was an active and continuously rewarded participant. In the present study, 192 Grade 1 children engaged in a lever-pulling task in a test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1972
1972
1991
1991

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…On the basis of their literature review, they posited that both genders show clear evidence of being “socially-attentive” but under different conditions. Particularly under competitive conditions, boys are far from being indifferent to other peoples' reactions, but rather respond to others' scrutiny by “showing off” and exerting more effort (Horner, 1970; Ryan & Strawbridge, 1969; Whiting & Edwards, 1973) much like the men in our study.…”
Section: What Is Causing the Gender Difference In Evaluative Influenc...mentioning
confidence: 57%
See 1 more Smart Citation
“…On the basis of their literature review, they posited that both genders show clear evidence of being “socially-attentive” but under different conditions. Particularly under competitive conditions, boys are far from being indifferent to other peoples' reactions, but rather respond to others' scrutiny by “showing off” and exerting more effort (Horner, 1970; Ryan & Strawbridge, 1969; Whiting & Edwards, 1973) much like the men in our study.…”
Section: What Is Causing the Gender Difference In Evaluative Influenc...mentioning
confidence: 57%
“…Maccoby & Jacklin, 1974). Recall the research summarized earlier that indicated that boys tend to respond to competition in particular with greater effort and a tendency to show off or exaggerate their own dominance (Horner, 1970; Omark, Omark, & Edelman, 1973; Ryan & Strawbridge, 1969; Whiting & Edwards, 1973). Furthermore, boys and men are more likely than girls and women to discount their failures on challenging tasks as being due to external forces such as bad luck or even a teacher's negative attitude toward them (e.g., Dweck & Bush, 1976; Eagly & Whitehead, 1972).…”
Section: Determinants Of the Gender Differencementioning
confidence: 99%
“…But precise examination of the items included in their listings in fact reveals power ful support for the thesis that boys have greater nAch and girls nApp. Many of the studies Maccoby and Jacklin (1974) list as contradicting the thesis do not in fact measure nAch (Kimball, 1973;Masters and Christy, 1973;Horner, 1972;Ryan and Strawbridge, 1969;Callard, 1968;Wyer, 1968;Field, 1951;Veroff, 1950) or nApp (Zimmerman and Bell, 1972;Crowder and Hohle, 1970;Todd and Nakamura, 1970;Montanelli and Hill, 1969;Unikel et al, 1969); and some, being adults' ratings of children's needs rather than direct measurements {Coates, 1973;Radin, 1973;Emmerich, 1971;Lansky and McKay, 1969;Hatfield et al. 1967), are subject to uncontrolled and undefined factors.…”
Section: The Effect O F Life Histories On Sex Differences In Behaviormentioning
confidence: 99%
“…Ford (see Ryan & Watson, 1968) offered a self-other blame hypothesis to explain this discrepancy suggesting that subjects who responded less vigorously following interruption had been led to believe that they were to blame for the interruption. This self-blame set was assumed to be inhibiting.Efforts thus far to test the self-other blame hypothesis have yielded inconsistent results (Pederson & McEwan, 1970;Ryan & Strawbridge, 1969). A further and more rigorous test of the self-blame hypothesis was devised to (a) use other blame conditions which would vary the social power of the interrupting agent and (b) employ an experimental task that allowed believable manipulation of the source of blame.The Haner-Brown marble game was presented to third-grade, white, middle-class males ages 8-10.…”
mentioning
confidence: 99%
“…Efforts thus far to test the self-other blame hypothesis have yielded inconsistent results (Pederson & McEwan, 1970;Ryan & Strawbridge, 1969). A further and more rigorous test of the self-blame hypothesis was devised to (a) use other blame conditions which would vary the social power of the interrupting agent and (b) employ an experimental task that allowed believable manipulation of the source of blame.…”
mentioning
confidence: 99%